Oncologic manifestations in children with neurofibromatosis type 1 in Turkey - İncecik, Faruk; Altunbaşak, Şakir; Hergüner, M. Özlem; Bayram, İbrahim; Küpeli, Serhan; Demirbilek, Hüseyin (The Turkish Journal of Pediatrics, 2013)
Children with neurofibromatosis type 1 (NF1) are predisposed to malignancies such as brain tumors, leukemia, and pheochromocytomas. The aim of this study was to evaluate malignancy in patients with NF1. We studied 120 patients with NF1 in this study. Demographic data from these patients were retrospectively reviewed. We found 20 malignancies in 19 patients in our study. Ten children with NF1 had optic glioma. Four children had solid central nervous system tumors (3 pilocytic astrocytomas, 1 glioblastoma multiforme). Three patients had myeloid malignancies (1 juvenile myelomonocytic leukemia, 1 acute myeloid leukemia, 1 acute lymphocytic leukemia). Hodgkin lymphoma, T-cell lymphoblastic lymphoma, and malignant triton tumor were found in one patient each. Patients with NF1 are predisposed to both benign and malignant tumors of neurogenic and non-neurogenic origin. Therefore, systematic medical follow-up in patients with NF1 is important.